MicroRNA-206 suppresses mesothelioma progression via the Ras signaling axis - Anand Singh; Nathanael Pruett; Roma Pahwa; Arushi P. Mahajan; David S. Schrump; Chuong D. Hoang (Elsevier, 2021)
Malignant pleural mesothelioma (MPM) is an incurable surface neoplasm with peculiar pathobiology. MPM proliferates by using the tyrosine-kinase-Ras pathway. Despite representing an attractive therapeutic target, there are no standard agent(s) specifically inhibiting Ras signaling adopted in clinical settings. We posited that biologic effects of microRNA (miRNA) can disrupt this molecular network. Using patient samples, cell lines, and murine tumor xenograft models, we confirmed specific genes in the Ras pathway are targeted by an MPM-associated miRNA and then examined its therapeutic effects. We verified significant and consistent downregulation of miR-206 in MPM tissues. When miR-206 is ectopically re-expressed in MPM cells and delivered to tumor xenografts in mice, it exerted significant cell killing by suppressing multiple components of the receptor-tyrosine-kinase-Ras-cell-cycle-signaling network; some of which were prognostic when overexpressed and/or have not been druggable. Of note, we validated CDK6 as a novel target of miR-206. Overall, this miR-206-targeting mechanism manifested as induced G1/S cell cycle arrest. In addition, we identified a novel MPM therapeutic combination by adding systemic-route abemaciclib with local-route miR-206, which showed additive efficacy translating to improved survival. Our pre-clinical study suggests a potential pathophysiologic role for, and therapeutic relevance of, miR-206 in MPM.